Social psychology - DeLamater, John D.; Collett, Jessica L. (New York, NY, USA : Routledge, Taylor & Francis Group, 2019)
This ninth edition of Social Psychology is an engaging exploration of the question, "what makes us who we are?" presented in a new, streamlined fashion. Grounded in the latest research, Social Psychology explains the methods by which social psychologists investigate human behavior in a social context and the theoretical perspectives that ground the discipline. Each chapter is designed to be a self-contained unit for ease of use in any classroom. This edition features new boxes providing research updates and "test yourself " opportunities, a focus on critical thinking skills, and an increased emphasis on diverse populations and their experiences.
Introduction to social psychology -- Research methods in social psychology -- Socialization through the life course -- Self and self-esteem -- Self-presentation and impression management -- Emotions -- Social perception and cognition -- Attitudes -- Symbolic communication and language -- Social influence and persuasion -- Altruism and prosocial behavior -- Aggression -- Deviant behavior and social reaction -- Interpersonal attraction and relationships -- Understanding groups -- Group processes -- Social structure and personality -- Glossary -- References -- Index.
Eighth edition published by Westview, 2015. First edition published by Harcourt, 1986
Includes bibliographical references and index.
CAS
Text in English
Keywords: Social psychology